Pemerolehan Bahasa Tulis Produktif Anak Kelompok Bermain dan Taman Kanak-kanak - Tadkiroatun Musfiroh (Humaniora, 2009)
Achieving Competence in children's productive written language (PWL) in playgroup and kindergarten indicates the existence of language acquisition, based on the 8 principles (differentiation, symbolization, integration, imitation, variation, inventarization-collection, repetition, generating). This acquisition process is categorized into 8 stages (scribble, linear repetitive, like-letter, random letter, early spellings, phonetic, transitional, conventional). The majority of subjects make handwriting which covers the forms of leaning-corrupted-interpolated-like-letter form, mirrored, and shadowed form. Children's PWL acquisition is related to children engagement in written language activities, social interaction, and exposure.